2012
DOI: 10.1515/jpm-2012-0074
|View full text |Cite
|
Sign up to set email alerts
|

Development of integrative autonomic nervous system function: an investigation based on time correlation in fetal heart rate patterns

Abstract: Emerging integrative ANS functions are reflected in increasing autocorrelation of fetal heart rate fluctuations over increasing time scales. The period from 21 to 31 gestational weeks seems to be critical to ANS development. Increasing long-time correlation is specific to active sleep states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Approximate entropy, a mathematical approach to quantify the complexity of a system, consists in the clinical application of chaos theory. Previous studies [ 55 , 56 ] had analyzed the relationship of ApEn with maturity of autonomous nervous system (ANS), thus emphasizing the relationship of a low value of ApEn with a lower Apgar score and metabolic acidosis. In our study, we found that ApEn progressively and significantly decreases in the <34th week group.…”
Section: Discussionmentioning
confidence: 99%
“…Approximate entropy, a mathematical approach to quantify the complexity of a system, consists in the clinical application of chaos theory. Previous studies [ 55 , 56 ] had analyzed the relationship of ApEn with maturity of autonomous nervous system (ANS), thus emphasizing the relationship of a low value of ApEn with a lower Apgar score and metabolic acidosis. In our study, we found that ApEn progressively and significantly decreases in the <34th week group.…”
Section: Discussionmentioning
confidence: 99%
“…While ultrasound-based techniques are generally based on the physical development and influenced by genetic variations, FHR provides a marker for neuro-physiological development of the fetus, since it reflects the Autonomic Nervous System (ANS) control of the cardiovascular system, which matures through the progress in pregnancy. Various linear, nonlinear and complexity-based FHR variability (FHRV) parameters have been found to be closely related to the fetal development (Van Leeuwen et al, 2003; Hoyer et al, 2009; Wallwitz et al, 2012; Hoyer et al, 2013; Tetschke et al, 2016). Vagal and sympathetic activity rhythms and their interactions has been traditionally attributed to different frequencies of FHR fluctuations and their ratios (European Society of Cardiology, 1996) which can be evaluated during fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…Autocorrelation and adjustment of the fetal heart rate (FHR) to fetal behavior develop over the second half of pregnancy along with the development of the fetal autonomic nervous system . FHR fluctuates somewhat in accordance with the maternal heart rate (MHR), with a circadian rhythm (i.e.…”
Section: Introductionmentioning
confidence: 99%